Contextualisation of instructional time utilising mobile social networks for learning efficiency: a participatory action research study for technical vocational education and training learners in South Africa - Dzvapatsva, Godwin Pedzisai (Department of Information Systems, 2021)
Despite the fact that some studies have shown a connection between learning efficiency and instructional time, there is lack of research that has been carried out within the Technical Vocational Education and Training sector with a particular focus on National Certificate Vocational programmes. To fill this gap, the current study utilised WhatsApp, an instance of a Mobile Social Network, in extending instructional time beyond the normal lecturing timetables with the objective of improving learning efficiency for NCV learners studying Computer Programming as a subject. To achieve the objective, a pragmatic approach was adopted in carrying out a participatory action research project. Qualitative data and quantitative data were collected concurrently in three phases using semi-structured interviews, questionnaire and documents. Thematic analyses and statistical analyses were applied to the data collected from five colleges in the Western Cape Province of South Africa. The findings of the study highlighted multiple issues: Firstly, awareness of instructional time phenomena was very minimal from the lecturers and the learners. Secondly, there were no formal interventions in place to recover or extend instructional time beyond the traditional college boundaries. In overall, the implementation of WhatsApp was well-supported at the five locations. However, statistical results from the five locations after implementation of the intervention were mixed. Results indicated an overall pass rate of 69.2% (n=54) of the total number of learners (N=78) who sat for the final examination. While pass rates at each of the other four locations was above 50%, the pass rate of the fifth location was considerably low (37%). The study generated three contributions to knowledge: practical, theoretical and methodological. Firstly, through the study, practical interventions were generated to assist learners outside the classes. Secondly, the thesis generated propositions from data and an integrated Mobile Social Network framework was developed which is expected to be a useful course of action for lecturers who want to improve learning efficiency through extending instructional time. A key methodological contribution has been the application of mixed methods choices in the collection, analyses of data and interpretation of results.